ENERGETIC POTENTIAL OF Phyllostachys bambusoides AS AN ALTERNATIVE SOURCE OF BIOMASS - Brand, Martha Andreia; Balduino Junior, Ailton Leonel; Friederichs, Gustavo; Cunha, Alexsandro Bayestorff da (Floresta, 2020)
In Brazil, Phyllostachys bambusoides has been used for the manufacture of laminated bamboo products and landscaping. However, studies of its energy quality are rare. Thus, this study aimed to determine the energetic quality of Phyllostachys bambusoides for the use of stems in the fresh form (chips) for direct burning, as charcoal and as briquettes. Its energy potential was also determined by mass and energy balance for each solid biofuel (chips, briquettes, and charcoal). The analyzes were carried out on five individuals (shoots) at 3 years of age, collected at experimental plantations in Frei Rogério, SC. In the stems the newly collected moisture was determined; specific gravity; chemical composition; immediate analysis and higher calorific value. In laboratory charcoal, gravimetric yield, apparent relative density, immediate analysis, and higher calorific value were determined. The briquettes, made in the laboratory, were evaluated through their apparent density and compressive strength. For the stems, charcoal, and briquettes the energy density was calculated and a flowchart composed of the mass balance was calculated and the thermal energy production potential for each 100 kg of biomass used in the production of each biofuel analyzed was calculated. The energy density of stems (1.87 Gcal.m-3), charcoal (2.60 Gcal.m-3), and briquettes (4.68 Gcal.m-3) varied significantly. The highest useful energy potential can be obtained from briquettes (0.304 Gcal), charcoal (0.184 Gcal) followed by stems (0.168 Gcal) for each 100 kg of bamboo harvested with a mean moisture content of 35%.